Analysis and Design of Lighting at the UNIMA Workshop Building - Pangestu, Prayogi; Seke, Fransiskus; Sangi, Nontje; Angmalisang, Harrychoon; Baharudin, Baharudin (JURNAL EDUNITRO Jurnal Pendidikan Teknik Elektro, 2023)
The need for natural and artificial lighting is a supporting component in daily human activities outside and inside buildings For lighting to be carried out properly it must meet the requirements stated in SNI and Minister of Health Regulation No 70 of 2016 concerning Standard Requirements for Light Intensity One of the goals of lighting in a building is to create sufficient lighting and reduce the risk of accidents Referring to the description the author is interested in understanding and researching further the existing lighting standards in the UNIMA Workshop building In evaluating the authors obtain research data by conducting case studies in which data is collected processed compared and analyzed The results showed that the light intensity in the UNIMA Workshop room had an average of 144 2 lux and in the work area of 191 06 lux < p>